“He’ll come with some sugar.” A qualitative study exploring the drivers and consequences of schoolgirls transactional sex behaviours - Thiaw, Yandé; Nyothach, Elizabeth; Zulaika, Garazi; van Eijk, Anna Maria; Fwaya, Eunice; Obor, David; Phillips-Howard, Penelope; Mason, Linda (Frontiers in Reproductive Health, 2024)
Transactional sex (TS) is common in areas of sub-Saharan Africa, motivated by reasons beyond financial support. Through this qualitative study we sought to understand the motivation driving TS among adolescent schoolgirls in rural western Kenya where rates are reportedly high. Identifying and understanding drivers within the local context is necessary for implementation of successful public health policy and programming to reduce the associated harms impacting health and wellbeing. To understand the drivers of sexual behaviors, individual views, and socio-cultural norms, we spoke with schoolgirls, male peers, parents and teachers. The three latter groups may influence, encourage, and shape girls’ views and behaviors and thus contribute to the perpetuation of cultural and societal norms. One hundred and ninety-nine participants took part across 20 FGDs; 8 comprised of schoolgirl groups, and 4 each of schoolboy, parent or teacher groups. Through thematic analysis, poverty emerged as the key driver of TS and a normative behaviour amongst secondary school girls. Subthemes including parental influence, need for menstrual pads, pressure from boda boda drivers, peer pressure, and blame were part of a complex relationship linking poverty with TS. We conclude that whilst TS is perceived as inevitable, normal and acceptable it is not really a choice for many girls. Exploring ways to encourage communication between families, including around menstruation, may help enable girls to ask for help in acquiring essential items. In addition, education at a community level may shift social norms over time and decrease the prevalence of age-disparate TS among schoolgirls and older, wealthier men in the community.